PENERAPAN MODEL PEMBELAJARAN KNISLEY BERBANTUAN MEDIA KERANJANG PENGURANGAN UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PESERTA DIDIK KELAS 2 SD SDN 165717 - Muthia Hakiki; Winda Nabila Sari Ritonga; Sahara Febriola; Melyani Sari Sitepu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the subtraction numeracy skills of second-grade students at SDN 165717 through the implementation of the Knisley learning model assisted by subtraction basket media. The background of this study is the low numeracy ability of students, particularly in subtraction, caused by conventional teaching methods that do not actively engage students in the learning process. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were second-grade students of SDN 165717. Data were collected through numeracy tests, observations of teacher and student activities, and documentation. The results showed that the application of the Knisley learning model assisted by subtraction basket media significantly improved students’ numeracy skills, as indicated by an increase in the average scores and the percentage of learning mastery from Cycle I to Cycle II. In addition, students’ participation and engagement during the learning process also improved. Therefore, it can be concluded that the Knisley learning model assisted by subtraction basket media is effective in improving the subtraction numeracy skills of second-grade students at SDN 165717.